2009
DOI: 10.1007/s00125-009-1318-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related psychological effects on metabolic control in type 2 diabetes mellitus

Abstract: Aims/hypothesis Women are at higher risk of diabetesrelated cardiovascular complications than men. We tested the hypothesis that there are sex-specific differences in glucometabolic control, and in social and psychological factors. We also examined the influence of these factors on glucometabolic control. Methods We examined 257 (126 men/131 women) consecutive patients (64±9 years, means±SD) of a metropolitan diabetes outpatient service employing clinical testing and standardised psychological questionnaires. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
3
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
(35 reference statements)
6
27
3
2
Order By: Relevance
“…(19,20) On the other hand, patients with a longer length of diagnosis may have further information on the disease, making them feel safer and more self-confident towards the proposed treatment. (21) Over time, treatment compliance can be neglected due to a lack of motivation and perception of effective results, lack of time, absence of family support, comorbidities, cultural issues, among others.…”
Section: Discussionmentioning
confidence: 99%
“…(19,20) On the other hand, patients with a longer length of diagnosis may have further information on the disease, making them feel safer and more self-confident towards the proposed treatment. (21) Over time, treatment compliance can be neglected due to a lack of motivation and perception of effective results, lack of time, absence of family support, comorbidities, cultural issues, among others.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that these subjective and psychological measures such as quality of life and symptom scores were the most important indicators for predicting various hard outcomes such as survival times, mortality, hospital readmission, therapy success or biochemical control after adjusting for known clinical factors in cancer patients, in patients with chronic diseases such as diabetes mellitus or heart failure and in the general population [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, pre-treatment subjective quality of life data may be the most reliable factor for guiding physicians to establish prognostic criteria for patients' therapy outcome [15,19].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of coping styles, in addition to distress, was conducted because of their central role in the human stress process, and specifically their influence on the individual's emotional reactions to demanding/stressful experiences, including disease [13]. Indeed, in diabetes, the interaction between coping style and psychological distress has been shown to influence glycaemic control [14][15][16]. Our secondary aims included: (1) an examination of the effects of distress and coping style on an additional healing outcome, i.e.…”
Section: Introductionmentioning
confidence: 99%